Knowledge Management and Employee Performance in the Information Technology Sector - Chalise, Mahananda; Biswakarma, Gangaram; Dhungana, Prabin (Journal of Business and Management, 2024)
Background: Knowledge management involves the identification, gathering, and organization of both explicit knowledge, such as documents and procedures, and tacit knowledge, including the skills and experience of individuals within an organization. Information technology is a knowledge-intensive industry, so knowledge management is crucial for employee performance. Objectives: The objective of this study is to examine the status of knowledge management practices within the IT sector, specifically knowledge creation, sharing, retention, and actionable knowledge support, and their influence on employee performance. Methods: This adopts a descriptive and explanatory research design. Purposively, it considered 310 employees working in IT companies in Nepal; 303 responses were considered for analysis. A questionnaire survey measured knowledge management with 27 items and employee (task) performance with six items. The study adopted PLS-SEM to analyze the data. Results: This study found that actionable knowledge support, knowledge sharing, and knowledge retention emerged as the primary influencers of employee performance within the IT sector. Specifically, active involvement in knowledge-sharing and retention contributes to employee performance. Among the factors, actionable knowledge support is vital for employee performance. However, a relationship between knowledge creation and performance was not found. Conclusion: This study helps improve our understanding of IT knowledge management dynamics in developing countries like Nepal, based on knowledge creation, sharing, retention, and actionable knowledge support. Future research on knowledge dynamics and performance may build on these findings. The knowledge-intensive nature of the IT sector affects employee performance. These findings could lay the groundwork for future research on knowledge dynamics and performance in this industry.